The effective management component is the basis for increasing innovative potential - L.V. Shytikova (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2021)
Modern Ukrainian enterprises are in great need of specialists-administrators who not only provide knowledge in the field of economics, entrepreneurship, but also can organize a daily innovation process that will ensure the achievement of strategic prices in the long run. The article considers the importance and general necessity of formation and constant development of the management sphere of agro-industrial enterprises, which is due to its priority, the need for further use of scientific approach to the formation, development and continuous improvement of management to further improve productivity in terms of active use of innovation potential. The disadvantage and impossibility of using extensive factors and traditional evolutionary processes and phenomena in the modern management process are determined. It is determined that on the basis of further development it will be an innovative approach that corresponds to the realities of the modern economy, allows companies to become leaders in fierce competition. The reasons that cause the crisis situation in agro-industrial production are analyzed, identified by modern problems of human resources management in the agro-industrial sector, taking into account the specific nature and characteristics of the work of agricultural workers. To ensure quality management in order to increase business success in an unstable situation, the company needs a reliable management mechanism at all stages of operation, which takes into account current trends in management theory and practice. The key task in today's innovative environment to ensure successful production of the enterprise is to focus on the formation of the effective management capacity, its continuous development and improvement in accordance with the established strategy of enterprise development, which should be considered as a prerequisite for effective use of labor potential, which will directly affect the efficiency of the economic entity. It is proved that effective innovations in the enterprise are carried out by a category of employees who hold positions of managers and specialists. More thorough research of qualitative and quantitative characteristics of this category of workers is offered, which determines their managerial professionalism: scientific and production experience; appropriate qualification; professional level; other qualities.